Statistical signature of active D-region HF heating in IRIS riometer data from 1994–2004 - Rietveld, Michael T.; Kero, A.; Enell, C.-F.; Ulich, Th.; Turunen, E.; Honary, F. H. (European Geosciences Union (EGU), 2007)
In this paper we study the effect of artificial HF heating on cosmic radio noise absorption in the D-region ionosphere. The effect has earlier been studied theoretically in idealised cases and without experimental verification. Here we present a 3-dimensional modelling of the effect, taking into account the directivity patterns of the vertical beam of the EISCAT Heater at Tromsø, Norway, and the intersecting beam of the IRIS imaging riometer at Kilpisjärvi, Finland. The heater-induced enhancement of cosmic radio noise absorption at the IRIS frequency (38.2 MHz) is estimated to be between 0.02 dB and 0.05 dB in the most representative model cases. However, a statistical study of IRIS data from a selected set of heating experiments carried out during the years 1994– 2004 shows that the median effect is between 0.002 dB and 0.004 dB, i.e. an order of magnitude less than theoretically predicted. This indicates that the actual HF heating effect at D-region altitudes is substantially overestimated by the present theory.